SOME MEDICINAL COMPOUNDS OBTAINED FROM KOVRAK (FERULA)PLANT WASTE (Scientific journal of the Fergana State University, 2023)
This paper presents the results of a study on the extraction of a sulfanilamide drug compound from kovrak plant wastes and the study of its diazotizing reaction with ferrocene.